2018
DOI: 10.3390/foods7120195
|View full text |Cite
|
Sign up to set email alerts
|

One Health, Fermented Foods, and Gut Microbiota

Abstract: Changes in present-day society such as diets with more sugar, salt, and saturated fat, bad habits and unhealthy lifestyles contribute to the likelihood of the involvement of the microbiota in inflammatory diseases, which contribute to global epidemics of obesity, depression, and mental health concerns. The microbiota is presently one of the hottest areas of scientific and medical research, and exerts a marked influence on the host during homeostasis and disease. Fermented foods and beverages are generally defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 134 publications
1
92
0
4
Order By: Relevance
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation of food with bacteria or yeast provides an anaerobic complex pathway, during which sugars are transformed by fermentation into ethanol and CO 2 (alcoholic fermentation) or lactic acid. The lactic acid bacteria produce foods, such as cheese, soymilk, yoghurt, pickles, bread, etc, and the alcoholic process produce wine and beers [110,111].…”
Section: Other Diet Componentsmentioning
confidence: 99%
“…During the past decade, however, microbial communities (or microbiomes) have been shown to play important roles in connecting the humans, plants, animals and environment (van Bruggen et al, 2019). Thus, recommendations have been made to extend the One Health concept to include the full breadth of microbes (Bell et al, 2018;Trinh et al, 2018;van Bruggen et al, 2019). Adopting a microbiome perspective may strengthen the One Health concept due to i) the vital services provided by microbiomes to overall ecosystem health, ii) the importance of microbiome processes for the transfer of energy, matter and chemicals between compartments along the food chain, and iii) the important contribution of microbiomes to the health of the different hosts and compartments.…”
Section: Introductionmentioning
confidence: 99%